2013
DOI: 10.1002/ijc.28142
|View full text |Cite
|
Sign up to set email alerts
|

Identification of oropharyngeal squamous cell carcinomas with active HPV16 involvement by immunohistochemical analysis of the retinoblastoma protein pathway

Abstract: Viral oncogene RNA expression is regarded as reliable biomarker to identify oropharyngeal squamous cell carcinomas (OPSCC) with active HPV16 involvement. This study addressed whether the expression profile of the cellular proteins p16INK4a , pRb, Cyclin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 51 publications
(177 reference statements)
9
67
2
1
Order By: Relevance
“…Holzinger et al found that 22% of HPV RNA+ OPSCC samples were p16−. In addition, among 14-21% of HPV− samples, the expression levels of p16 were upregulated with no evidence of an HPV-16 transforming infection [39]. In our study, we …”
Section: Tong Et Al: Prognostic Significance Of Hpc In Laryngeal Cancersupporting
confidence: 58%
“…Holzinger et al found that 22% of HPV RNA+ OPSCC samples were p16−. In addition, among 14-21% of HPV− samples, the expression levels of p16 were upregulated with no evidence of an HPV-16 transforming infection [39]. In our study, we …”
Section: Tong Et Al: Prognostic Significance Of Hpc In Laryngeal Cancersupporting
confidence: 58%
“…HPV-induced HNSCC are associated with low pRb. Therefore, low pRB may represent a surrogate biomarker for HPV association [36]. However, there was no association between p16 status and survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the 3 methods used in our study to prove the presence of HPV DNA (applied to patients [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], it seems that HPV-DNA PCR on cytological suspension has higher sensitivity (8 positive cases) than HPV-DNA PCR using FFPE tissue specimens (7 positive cases) and HPV-DNA ISH (4 positive cases), respectively. However, the number of patients that we analyzed with all 3 methods was too small to finally evaluate the diagnostic sensitivity of these methods.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19] Consequently, general anesthesia is necessary for tissue sampling in most cases. Brush biopsies of macroscopically suspect lesions, as performed in our study, are a practical, noninvasive, cheap, and relatively painless alternative Original Article method for the collection of cellular material from the oral cavity to perform further diagnostics (eg, the evaluation of cytomorphology, immunostaining, or PCR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation